Production and Performance of Al-Ti-C Grain Refiners with Addition of K2TiF6 and Elemental Carbon - Ambarkutuk, Aysin; Daglilar, Sibel (CARL HANSER VERLAG, 2014)
AlTiC master alloys were improved greatly and used as a new type in grain refinement of aluminum and aluminum alloys. In the present work, Al-Ti-C grain refiners with different Ti/C ratios were in-situ produced by the addition of K2TiF6 and elemental carbon powder mixture to the commercial pure aluminum. The effects of casting temperature and Ti/C ratio on the grain refinement process were investigated by the so-called Alcoa Cold Finger test and respective optimum conditions were determined. The results indicate that the produced Al-Ti-C master alloys contain TiC and TiAl3 particles within the aluminum matrix. The proper conditions for evaluating the efficiency of the produced Al-Ti-C master alloy to obtain a minimum grain size are: Temperature of 1300 degrees C, holding time of 20 minutes, and a Ti/C 0.60 wt.-%
Keywords: Materials testing; aluminium; Al-Ti-C grain refiners; K2TiF6; elemental carbon; REFINING EFFICIENCY; Materials Science